Troublemaker - Clements, Andrew, 1949-; Elliott, Mark, 1967- (New York : Atheneum Books for Young Readers, 2011)
When his older brother gets in serious trouble, sixth-grader Clay decides to change his own mischief-making ways, but he cannot seem to shake his reputation as a troublemaker.
School Library Journal, July 2011
Publisher's Weekly, May 2011
Booklist, June 2011
Horn Book, July 2011
Bulletin (Center for Children's books), July 2011
Kirkus Review, June 2011
Keywords: Human behavior -- Juvenile fiction; Schools -- Juvenile fiction; Brothers -- Juvenile fiction; Behavior -- Fiction; Schools -- Fiction; Brothers -- Fiction; Human behavior -- Fiction; School stories; Brothers -- Fiction